2021
DOI: 10.1093/femsyr/foab041
|View full text |Cite
|
Sign up to set email alerts
|

Response to sulfur in Schizosaccharomyces pombe

Abstract: Sulfur is an essential component of various biologically important molecules, including methionine, cysteine, and glutathione, and it is also involved in coping with oxidative and heavy metal stress. Studies using model organisms, including budding yeast (Saccharomyces cerevisiae) and fission yeast (Schizosaccharomyces pombe), have contributed not only to understanding various cellular processes but also to understanding the utilization and response mechanisms of each nutrient, including sulfur. Although fissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Further, ecl family genes are required to induce sporulation during sulfur starvation and induce sexual differentiation during iron or zinc starvation (Ohtsuka & Aiba, 2017 ; Ohtsuka et al, 2017 ). Although sulfur starvation induces autophagy and sporulation, and extends CLS, similarly to nitrogen starvation, it leads to neither G 1 arrest nor mating (Corral‐Ramos et al, 2021 ; Ohtsuka et al, 2017 , 2021d ; Shimasaki et al, 2020 ). Recently, it was reported that ecl family genes inhibit TORC1 activity (Ohtsuka et al, 2022a ).…”
Section: Molecular Basis Of Sporulation By S Pombementioning
confidence: 99%
“…Further, ecl family genes are required to induce sporulation during sulfur starvation and induce sexual differentiation during iron or zinc starvation (Ohtsuka & Aiba, 2017 ; Ohtsuka et al, 2017 ). Although sulfur starvation induces autophagy and sporulation, and extends CLS, similarly to nitrogen starvation, it leads to neither G 1 arrest nor mating (Corral‐Ramos et al, 2021 ; Ohtsuka et al, 2017 , 2021d ; Shimasaki et al, 2020 ). Recently, it was reported that ecl family genes inhibit TORC1 activity (Ohtsuka et al, 2022a ).…”
Section: Molecular Basis Of Sporulation By S Pombementioning
confidence: 99%
“…[203] In addition to the TORC1 pathway, several signaling pathways, including the PKA, Pmk1, and Sty1 pathways, regulate CLS in S. pombe. [204][205][206][207] Pmk1 is a MAPK that is a core effector of the cell integrity pathway and an extracellular signal-regulated kinase ERK ortholog. [208,209] The Pmk1 pathway is expected to have a negative effect on CLS extension because deletion of MAPK, MAPKK, and MAPKK kinase (MAPKKK) leads to extended CLS.…”
Section: Ethylenediaminetetraacetic Acidmentioning
confidence: 99%
“…Yeast can use sulfate as a source of sulfur, a necessary nutrient for growth, and an essential component of various biologically important molecules such as methionine, cysteine, and glutathione (Huang et al, 2017; Ohtsuka et al, 2021c). In S. pombe , sulfur starvation promotes nuclear accumulation of the transcription factor Zip1, which directly induces ecl1 + transcription (Ohtsuka et al, 2017).…”
Section: Signal Network Involved In Ecl Family Protein Inductionmentioning
confidence: 99%
“…Sulfur starvation induces ecl1 + expression by Zip1, leading to autophagy, sporulation, cell cycle arrest at G 2 , and CLS extension, whereas this starvation does not lead to G 1 arrest or mating (Corral‐Ramos et al, 2022; Ohtsuka et al, 2017, 2021c; Shimasaki et al, 2020).…”
Section: Signal Network Involved In Ecl Family Protein Inductionmentioning
confidence: 99%